The Concept of q-Cycle and Applications. (26th February 2014) - Pintoptang, Umarin; Tadee, Suton; Laohakosol, Vichian
Abstract : The concept ofq -cycle is investigated for its properties and applications. Connections with irreducible polynomials over a finite field are established with emphases on the notions of order and degree. The results are applied to deduce new results about primitive and self-reciprocal polynomials.